Pengaruh Motivasi Konsumen, Persepsi Kualitas, Sikap Konsumen, dan Brand Image Pada Keputusan Pembelian Komputer Tablet Apple Ipad Pada Emax Apple Store Surabaya - Sumiati Sumiati (Universitas 17 Agustus 1945 Surabaya, 2014)
Abstract:Â Today, tablet computer business world is growing and developing very rapidly. In Indonesia, the most striking development is the competition of two famous vendors, that be the market leader in table computer market, namely between Apple with its iPad product, and Samsung with its Galaxy tab product that having Android OS. The both tablet computers so steal Indonesian attention, in particular the gadget lovers. With the different OS specifications and uses, of course, each of products has its advantages and disadvantages. Every product has certain uniqueness, which may attract the consumer interest; it also includes the selling price. Likewise with the EMAX Apple Store of Surabaya that always wants to attract the consumer interest to choose the Apple iPad Tablet Computer products.From the result of testing on the model in this research, by using random sampling, structural equation model (SEM) analysis, and the assistance of software Amos 20, on 200 respondents, it has been able to explain the correlation of consumer motivation, quality perception, consumer attitude, and Brand Image, on the decision of Apple iPad Tablet computer buying at EMAX Apple Store of Surabaya.In this research, it was obtained 1) Consumer motivation had positive effect on the decision of Apple iPad tablet computer buying, 2) Quality perception had positive effect on the decision of Apple iPad tablet computer buying, 3) Consumer attitude had positive effect on the decision of Apple iPad tablet computer buying, 4) Brand image had positive effect on the decision of Apple iPad tablet computer buying, 5) Consumer motivation, Quality perception, Consumer attitude, and Brand image simultaneously had positive effect on the decision of Apple iPad tablet computer buying at EMAX Apple Store of Surabaya.Key words: EMAX Apple Store, consumer motivation, quality motivation, consumer attitude, brand image, buying decision.